Respuesta :

To find the midpoint, add the two x values together and divide by 2, and then do the same with the Y values.

-3 + 3 = 0

0 / 2 = 0, the X value is 0

-1 + 3 = 2

2/2 = 1, the Y value is 1

The midpoint would be (0,1)

Answer:

The answer to your question is (0, 1)

Step-by-step explanation:

Data

B (3, -1)

C (-3, 3)

Formula

[tex]Xm = \frac{x1 + x2}{2}[/tex]

[tex]Ym = \frac{y1 + y2}{2}[/tex]

Substitution and simplification

[tex]Xm = \frac{3 - 3}{2}[/tex]

[tex]Xm = \frac{0}{2}[/tex]

      Xm = 0

[tex]Ym = \frac{-1 + 3}{2}[/tex]

[tex]Ym = \frac{2}{2}[/tex]

      Ym = 1

Result

           (0, 1)

ACCESS MORE